Snake and Ladder Game Intervention to Reduce Anxiety in Hospitalized Children - Marsella Putri Sulung (Journal of Applied Holistic Nursing Science, 2024)
Backgraund : Typhoid fever is a disease that affects the digestive tract, leading to an infection of the small intestine caused by the Salmonella typhi bacteria. Typhoid treatment often requires hospitalization, which, in addition to impacting the physical healing process, can also affect the psychological well-being of children, particularly in terms of anxiety.To reduce anxiety, snake and ladder game therapy can be utilized. This study aims to provide information about the anxiety experienced by preschool-aged children. Methods : The research employs a descriptive case study approach. The subjects of the study consist of two children with similar criteria: pediatric typhoid fever patients experiencing anxiety issues. Data collection techniques include interviews, observations, and completing case study instruments over a period of three days in the treatment room. Result : This study shows that play therapy reduces anxiety in pediatric patients with typhoid fever. The intervention using the snake and ladder game successfully decreased anxiety levels 1 over three days. Conclusion : Snake-and-ladder game therapy effectively reduced anxiety levels in typhoid fever patients, showing significant improvement from moderate to mild anxiety after three days.